Ekstraksi Bunga Kecombrang dan Rosela dengan Metode MAE serta Aplikasinya pada Produk Permen Jelly - Regita Puspitasari; Rifda Naufalin; Ike Sitoresmi Mulyo Purbowati; Rumpoko Wicaksono (Institut Pertanian Bogor, 2024)
Research in recent years has shown the antioxidant activities of kecombrang and roselle flowers, as well as the antibacterial properties of kecombrang, so these materials have potentials to be developed as a functional food product. With an easy manufacturing process and basic ingredients that are easy to obtain, jelly candy is one of the preparations that can be applied to kecombrang and roselle flower extracts. This research aims 1) to determine the effect of variations in microwave-assisted extraction time and power on the physicochemical characteristics of the resulting extract and 2) to determine the effect of variations in the ratio of kecombrang and roselle flower extracts as ingredients for jelly candy products on the physical, chemicall, and sensory characteristics of the product. Research on the extraction of kecombrang and roselle flower powder used a randomized block design (RBD). Treatment consisted of two factors: 1) extraction power (150, 200, and 250 watts); 2) extraction time (3, 5, and 7 minutes). The data obtained were analyzed using the SPSS program. The analysis results showed that the best extraction of kecombrang and roselle flowers were at 250 watts of power and 5 minutes of extraction time. The best extraction results are then processed into jelly candy with the best sensory results in the 15%:25% sample. This jelly candy product contains reduced sugar levels of 12.41%, vitamin C levels of 23.58 mg/100g, total phenol levels of 47.58 mg/100g, total flavonoid levels of 18.80 mg/100g, and antioxidant activity amounting to 28.24 mg/100g. Keywords: extraction, jelly candy, kecombrang, MAE, rosella